2019
DOI: 10.32947/ajps.v19i2.556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin Supplement on Pulmonary Functions, Total and Differential White Blood Cell Count, Serum Level of Leptin and Body Mass Index in a Sample of Iraqi Patients with Chronic Bronchial Asthma

Abstract: Asthma is a heterogeneous disease, usually characterized by chronic airway inflammation together with increased oxidative stress that lead to clinical symptoms of asthma.    Obesity is a known risk factor of asthma as the obesity is correlated with systemic inflammation and airway restriction. Curcumin, a natural product derived from the rhizomes of Curcuma longa (Turmeric), has a wide range of beneficial properties including anti-inflammatory and weight reducing agent. This study was designed to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In a study by Jusufovic et al ( 2017 ), which evaluated the effect of curcumin plus inhaled corticosteroids in adults with known asthma, a significant change in FEV1 was observed in the curcumin group after 2 months. Moreover, in a study by Khdair et al ( 2019 ) involving obese asthmatic patients with the chronic bronchial disease, curcumin improved the FEV1 and the FEV1/FVC ratio.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study by Jusufovic et al ( 2017 ), which evaluated the effect of curcumin plus inhaled corticosteroids in adults with known asthma, a significant change in FEV1 was observed in the curcumin group after 2 months. Moreover, in a study by Khdair et al ( 2019 ) involving obese asthmatic patients with the chronic bronchial disease, curcumin improved the FEV1 and the FEV1/FVC ratio.…”
Section: Discussionmentioning
confidence: 94%
“…asthma, a significant change in FEV1 was observed in the curcumin group after 2 months. Moreover, in a study by Khdair et al (2019) involving obese asthmatic patients with the chronic bronchial disease, curcumin improved the FEV1 and the FEV1/FVC ratio.…”
Section: Effects Of Nano-curcumin On Pulmonary Functionmentioning
confidence: 94%
“…In a prospective randomized controlled interventional study, 23 asthmatic patients were assigned to receive conventional therapy for asthma plus curcumin capsules for 2 months. The results revealed significant improvement in FEV1 and FEV1/forced vital capacity (FVC) in patients after 2 months 61 . A placebo‐controlled, single‐blind study on 150 nonsmokers patients with asthma showed an improvement in FEV1% after 3‐month treatment with curcumin 62,63 …”
Section: Resultsmentioning
confidence: 99%
“…The results revealed significant improvement in FEV1 and FEV1/forced vital capacity (FVC) in patients after 2 months. 61 A placebo-controlled, single-blind study on 150 nonsmokers patients with asthma showed an improvement in FEV1% after 3-month treatment with curcumin. 62,63 In Asian older adults, increasing levels of curcuminsrich curry intake (at least once monthly) were associated with higher mean adjusted FEV1 and FEV1/FVC%.…”
Section: Clinical Evidencementioning
confidence: 99%